1988
DOI: 10.1182/blood.v72.1.89.89
|View full text |Cite
|
Sign up to set email alerts
|

Partial chimerism after T-cell-depleted allogeneic bone marrow transplantation in leukemic HLA-matched patients: a cytogenetic documentation

Abstract: We evaluated serially by cytogenetics the blood and marrow chimerism of 38 leukemic recipients of HLA-matched bone marrow transplants (BMT) who were prepared by high doses of alkylating agents and fractionated total- body irradiation (2.2 Gy X 5). Donor or host mitoses were identified by examination of sex chromosomes in 32 patients or by evaluation of the polymorphism of other chromosomes after specific banding in six patients. Twenty-four patients were recipients of untreated BMT, and 14 were recipients of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Using red blood cell phenotyping and cytogenetic analysis of the bone marrow, evaluation of chimaerism at 6 months and 1 year after BMT showed high incidences of mixed chimaerism. These findings are comparable with other chimaerism studies after transplantation with T-cell-depleted marrow grafts (Bertheas et al, 1988;Roy et al, 1990;Schattenberg et al, 1989). In a previous analysis we showed that mixed chimaerism at 6 months after BMT was not correlated with higher incidence of relapse (Schattenberg et al, 1990.…”
Section: Discussionsupporting
confidence: 91%
“…Using red blood cell phenotyping and cytogenetic analysis of the bone marrow, evaluation of chimaerism at 6 months and 1 year after BMT showed high incidences of mixed chimaerism. These findings are comparable with other chimaerism studies after transplantation with T-cell-depleted marrow grafts (Bertheas et al, 1988;Roy et al, 1990;Schattenberg et al, 1989). In a previous analysis we showed that mixed chimaerism at 6 months after BMT was not correlated with higher incidence of relapse (Schattenberg et al, 1990.…”
Section: Discussionsupporting
confidence: 91%
“…The development of molecular techniques to quantify chimaerism, has shed new light on the kinetics of T-cell and myeloid cell engraftment. Persisting mixed chimaerism after SCT has been associated with relapse in some, but not all studies (Petz et al, 1987;Bertheas et al, 1988;Schattenberg et al, 1989;Offit et al, 1990;Schaap et al, 1997;Schaap et al, 2002). However, these investigators evaluated only whole blood chimaerism, and as a consequence, little is known about lineage-specific donor engraftment -especially in the context of myeloablative TCD transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Results are available within 6 h, enabling informed clinical decisions to be made within the same working day. Many methods have been developed to evaluate chimaeric status after allogeneic BMT (Blazer et al, 1985;Bertheas et al, 1988;Leclair et al, 1995). Problems of specificity, sample size and complex methodology have meant that these methods have mainly now been superseded by microsatellite PCR analyses (Lawler et al, 1989;Roth et al, 1990;Roy et al, 1990;Roux et al, 1992;MacKinnon et al, 1994;Molloy et al, 1996).…”
Section: Discussionmentioning
confidence: 99%